Resting State fMRI Reveals Increased Subthalamic Nucleus and Sensorimotor Cortex Connectivity in Patients with Parkinson’s Disease under Medication - Shen, Bo; Gao, Yang; Zhang, Wenbin; Lu, Liyu; Zhu, Jun; Pan, Yang; Lan, Wenya; Xiao, Chaoyong; Zhang, Li (Frontiers in Aging Neuroscience, 2017)
Functional connectivity (FC) between the subthalamic nucleus (STN) and the sensorimotor cortex is increased in off-medication patients with Parkinson’s disease (PD). However, the status of FC between STN and sensorimotor cortex in on-medication PD patients remains unclear. In this study, resting state functional magnetic resonance imaging was employed on 31 patients with PD under medication and 31 healthy controls. Two-sample T test was used to study the change in FC pattern of the STN，the FC strength of the bilateral STN was correlated with overall motor symptoms, while unilateral STN was correlated with offside motor symptoms. Both bilateral and right STN showed increased FC with the right sensorimotor cortex, whereas only right STN FC was correlated with left-body rigidity scores in all PD patients. An additional subgroup analysis was performed according to the ratio of mean termor scores and mean postural instability and gait difficulty(PIGD) scores, only the PIGD subgroup showed the increased FC between right STN and sensorimotor cortex under medication. Increased FC between the STN and the sensorimotor cortex was found, which was related to motor symptom severity in on-medication PD patients. Anti-PD drugs may influence the hyperdirect pathway to alleviate motor symptoms with the more effect on the termor subtype.